2001
DOI: 10.1080/03079450124811
|View full text |Cite
|
Sign up to set email alerts
|

Pigeon circovirus infection: Pathological observations and suggested pathogenesis

Abstract: Pigeon circovirus infection (PiCV) was diagnosed by light and transmission electron microscopy in 15 birds from five lofts in western France. Histopathological findings were suggestive of primary bursotropism of pigeon circovirus, followed by secondary systemic spread from the bursa of Fabricius, particularly to non-bursal lymphoid organs. The last stage of the disease was associated with various secondary (particularly bacterial) infections. In situ detection of apoptosis in the bursa of Fabricius indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 18 publications
2
55
0
1
Order By: Relevance
“…Lymphatic tissues, such as the bursa of Fabricius and spleen, more frequently contained detectable PiCV DNA, while inclusion bodies in the bursa of Fabricius similar to those seen in our study have been seen in pigeons infected with PiCV (Shivaprasad et al ., 1994;Abadie et al ., 2001;Roy et al ., 2003). Further investigations using in situ hybridization techniques will be needed to demonstrate that PiCV DNA is present in these inclusion bodies.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphatic tissues, such as the bursa of Fabricius and spleen, more frequently contained detectable PiCV DNA, while inclusion bodies in the bursa of Fabricius similar to those seen in our study have been seen in pigeons infected with PiCV (Shivaprasad et al ., 1994;Abadie et al ., 2001;Roy et al ., 2003). Further investigations using in situ hybridization techniques will be needed to demonstrate that PiCV DNA is present in these inclusion bodies.…”
Section: Discussionmentioning
confidence: 99%
“…The progress in molecular biology techniques facilitated rapid and accurate detection of infectious diseases. As a result, cases of PiCV infections in pigeons were subsequently reported in various countries and regions, including Northern Ireland (Smyth & Caroll 1995;Todd et al 2001), Germany (Mankertz et al 2000;Raue et al 2005), Italy (Coletti et al 2000;Franciosini et al 2005), France (Abadie et al 2001), Czech Republic (Taras et al 2003), Belgium (Duchatel et al 2005, Poland (Wieliczko et al 2005;Stenzel et al 2012Stenzel et al , 2014a, Slovenia (Krapez et al 2012), Hungary (Cs agola et al 2012), United Arab Emirates (Ledwo n et al 2011), Iran (Mahzounieh et al 2014, Taiwan (Liao et al 2015), China (Zhang et al 2011;Phan et al 2013;Zhang et al 2015a), Japan (Yamamoto et al 2015) and the USA (Roy et al 2003) (Figure 1). In most reports, the virus was detected in the pigeon species of Columba livia domestica, but in several cases, PiCV genetic material was also detected in Senegal doves (Streptopelia senegalensis) and collared doves (Streptopelia decaocto) (Kub ı cek & Taras 2005;Todd et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…PiCV was first documented in Canada in 1986 (Woods et al, 1994); since then, several outbreaks have been reported in many countries, including Northern Ireland (Smyth & Carroll, 1995;Todd et al, 2001), England (Gough & Drury, 1996), Germany (Mankertz et al, 2000;Raue et al, 2005;Soike, 1997), France (Abadie et al, 2001), Belgium (Duchatel et al, 2006), China (Yu et al, 2009), Hungary (Cságola et al, 2012 and Italy (Coletti et al, 2000;Franciosini et al, 2005). A comprehensive study has demonstrated that PiCV infection is associated with a multifactorial disease known as young pigeon disease syndrome (YPDS) possibly by inducing immunosuppression in infected birds (Raue et al, 2005;Schmidt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%